A polyimide film with high peel strength and preparation method thereof
By compounding the modified silica aerogel with the polyimide film, the compatibility and surface roughness of the polyimide film and the epoxy adhesive sheet are improved, and the bonding between the polyimide film and the epoxy is solved. The problem of low peel strength of the sheet is solved, and high peel strength and other properties are maintained.
Patent Information
- Application Number
- CN202211544223.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-11-29
AI Technical Summary
In the prior art, the peel strength between the polyimide film and the epoxy adhesive sheet is low, making it difficult to meet product requirements.
By compounding the modified silica aerogel with the polyimide film, the compatibility of the film surface with the epoxy adhesive sheet is improved, and the roughness of the film surface is increased through modification treatment, thereby improving the peel strength.
It achieves high peel strength between the polyimide film and the epoxy adhesive sheet, with the peel strength reaching more than 9N/cm, and maintaining other properties of the film, such as tensile strength, elongation at break and electrical strength.
Smart Images

Figure BDA0003970036800000081 
Figure BDA0003970036800000091 
Figure BDA0003970036800000092
Abstract
Description
Technical Field
[0001] The invention relates to a polyimide material, in particular to a polyimide film with high peeling strength and a preparation method thereof. Background Art
[0002] Polyimide (PI) film is widely used as an insulating material for flexible printed circuit boards and rigid-flexible printed circuit boards because of its excellent mechanical properties, electrical insulation and dimensional stability, and high temperature resistance. When used for flexible printed circuit boards, epoxy resin must be coated on the surface of the polyimide film first, and then pressed with copper foil. The peel strength of polyimide and copper foil can reach 8 to 12 N / cm. Rigid-flexible printed circuit boards are different from flexible printed circuit boards. Rigid-flexible printed circuit boards are made by interconnecting the flexible printed circuit board substrate with the rigid printed circuit board substrate in different areas using a non-flowing semi-cured sheet (epoxy adhesive sheet). It not only has the characteristics of flexible printed circuit boards that can be bent, folded, rolled, and moved and stretched at will in three-dimensional space, but also has the functions of rigid printed circuit boards to connect wires and cables between endpoints and carry components. At present, epoxy adhesive sheets are mainly made of glass fiber cloth impregnated with epoxy resin, which has good adhesion. When connecting rigid-flex substrates, one side is bonded to copper foil and the other side is bonded to the surface of PMDA-ODA thermosetting polyimide film through a hot pressing process. Since there are tiny copper teeth on the surface of copper foil, the epoxy adhesive sheet has a strong bonding force with the copper foil, while the surface energy of the polyimide film is low. Even if the surface of the polyimide film is corona treated, the peel strength between it and the epoxy adhesive sheet is only about 2 to 4 N / cm, which is difficult to meet product requirements.
[0003] In the prior art, there are many methods to improve the peeling strength between polyimide film and copper foil or other substrates, but they are difficult to be applied to improve the peeling strength between polyimide film and epoxy adhesive sheet. For example, the invention patent with announcement number CN101098909B uses a flexible diamine containing 4,4'-diaminodiphenyl ether and bis(4-(4-aminophenoxy)phenyl)propane and aromatic dianhydride to prepare a thermosetting polyimide film, and a thermoplastic polyimide layer is coated on the surface of the thermosetting polyimide film as an adhesive layer to obtain an adhesive film. The experiment shows that the metal copper foil peeling strength of the laminate is increased by 85% by laminating the adhesive film with copper foil, reaching more than 15N / cm in the 90-degree direction and more than 10N / cm in the 180-degree direction. However, after being coated with thermoplastic polyimide, the imidization temperature of the polyimide composite film is as high as 300°C or more. Although it can be used in flexible printed circuit boards and pressed with copper foil under protective gas conditions, it is not suitable for bonding with epoxy adhesive sheets in rigid-flexible printed circuit boards. In addition, there are also reports that the peel strength is improved by coating the polyimide film with a surface treatment agent, such as the invention patent with publication number CN106432723A, which extracts the prepared PMDA-ODA thermosetting polyimide film in methanol for 1 to 10 minutes, then uses plasma surface treatment to roughen it for 1 to 9 minutes, and then immerses it in an aqueous solution containing 10% acrylamide, and then uses ultraviolet radiation at 50 to 70°C, and finally dries the water. The polyimide film obtained by this invention has a peel strength of more than 10N / cm with copper foil, but its process is complicated, and the heat resistance and flexibility of acrylamide are poor, and the product life is short. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a polyimide film with high peeling strength and a preparation method thereof, which can effectively improve the bonding force between the film and the epoxy adhesive sheet, in view of the deficiencies in the prior art.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A method for preparing a polyimide film with high peel strength comprises the following steps:
[0007] 1) dispersing silica aerogel in anhydrous ethanol, modifying it with terminal hydroxyl polydimethylsiloxane and diethoxydimethylsilane in sequence, or modifying it with terminal hydroxyl polydimethylsiloxane and dimethyldimethoxysilane in sequence to obtain a dispersion, recovering the solvent from the dispersion to obtain a modified silica aerogel;
[0008] 2) dispersing the modified silica aerogel in a polar aprotic solvent, and then adding aromatic diamine and aromatic dianhydride to carry out polymerization reaction to obtain a polyamic acid solution;
[0009] 3) The obtained polyamic acid solution is prepared into a polyimide film, and the obtained film is subjected to or not subjected to corona treatment to obtain the polyimide film with high peel strength.
[0010] In step 1) of the above preparation method, the amount of anhydrous ethanol used is generally controlled so that the concentration of silica aerogel in the system is less than or equal to 15wt%, which is conducive to the dispersion and modification of silica aerogel in the subsequent modification process. It is further preferred that the amount of anhydrous ethanol used is controlled so that the concentration of silica aerogel in the system is 5-11wt%. The particle size of the silica aerogel is preferably nanometer to micrometer, and more preferably 10nm to 1μm. The modification operation is the same as the prior art, such as performing ultrasound and / or shearing after adding terminal hydroxyl polydimethylsiloxane and diethoxydimethylsilane or dimethyldimethoxysilane. Based on the volatility of anhydrous ethanol, it is preferred that the modification is carried out under closed conditions.
[0011] The applicant found in the experiment that the molecular weight and dosage of terminal hydroxyl polydimethylsiloxane, and the dosage of diethoxydimethylsilane or dimethyldimethoxysilane will affect the modification effect and the adhesion between the final polyimide film and the epoxy adhesive sheet. According to the test results, the applicant believes that it is more advantageous to use terminal hydroxyl polydimethylsiloxane with a molecular weight of 500 to 50,000. Under the premise of the above molecular weight, the dosage of the terminal hydroxyl polydimethylsiloxane is preferably 5 to 20 wt% of the silica aerogel, and more preferably 10 to 15 wt%; and the dosage of diethoxydimethylsilane or dimethyldimethoxysilane is more suitable to be 0.1 to 2 wt% of the silica aerogel.
[0012] In step 1) of the above preparation method, the solvent (anhydrous ethanol) in the dispersion is recovered by conventional methods. For example, the outlet of the container containing the dispersion can be connected to an exhaust device or a device that can realize gas or steam condensation recovery. The dispersion is heated (the container containing the dispersion can be heated, or the dispersion can be heated by ultrasound) to volatilize and discharge the anhydrous ethanol in the dispersion, thereby promoting the precipitation of solids. The precipitated solids are modified silica aerogel powders.
[0013] In step 2) of the above preparation method, the modified silica aerogel is dispersed in a polar aprotic solvent by conventional methods, such as ultrasound and / or shearing. In this step, a conventional in-situ polymerization method is used to prepare a polyamic acid solution (also called polyamic acid resin or polyamic acid resin solution), wherein the selection and dosage of aromatic diamine and aromatic dianhydride, the selection and dosage of polar aprotic solvent, the temperature and time of polycondensation reaction, etc. are the same as those in the prior art. Specifically:
[0014] As the aromatic diamine, 4,4'-diaminodiphenyl ether (ODA) or 1,4-diaminobenzene (PDA) or a combination thereof is preferred.
[0015] As the aromatic dianhydride, pyromellitic dianhydride (PMDA) or 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) is preferred, or a combination of the two.
[0016] The molar ratio of the aromatic diamine to the aromatic dianhydride is preferably controlled within a range of 1:0.990 to 1:0.998.
[0017] The polar aprotic solvent may be one or a combination of two or more of N,N-dimethylacetamide (DMAC), N,N-dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), N,N-diethylacetamide and N,N-diethylformamide. The amount of the polar aprotic solvent may be such that when the aromatic diamine, tetracarboxylic dianhydride and the polar aprotic solvent react to form a polyamic acid solution, the solid content in the polyamic acid resin solution is controlled to be 17-22wt%, preferably 19-20wt%.
[0018] In step 2) of the above preparation method, the amount of the modified silica aerogel is 0.5-3 wt % of the total amount of the aromatic diamine and the aromatic dianhydride. The applicant's test results show that excessive amount of modified silica aerogel will reduce the mechanical properties of the obtained film.
[0019] In step 3) of the above-mentioned preparation method, the obtained polyamic acid solution is prepared into a polyimide film by an existing well-known method, such as a thermal imidization method or a chemical imidization method. Specifically, the obtained polyamic acid solution can be subjected to conventional defoaming, cast film, stretching and imidization processes to prepare a polyimide film. Preferably, the stretching ratio can be 1 to 15%, and the imidization temperature is gradually increased from 120°C to 450°C, and then gradually cooled to room temperature. In this step, when the obtained polyimide film is used for bonding with an epoxy adhesive sheet, whether or not corona treatment is performed has no effect on the bonding force between the obtained film and the epoxy adhesive sheet, and the peel strength can reach more than 9N / cm; but when the obtained film is used for bonding with a metal substrate such as copper foil, corona treatment is required before the film is rolled up to obtain a satisfactory peel strength.
[0020] The present invention also includes a polyimide film with high peel strength prepared by the above method. The peel strength of the film with the epoxy adhesive sheet (the film has not been corona treated before rolling) is ≥9N / cm, and the peel strength with the copper foil (the film has been corona treated before rolling) is ≥13N / cm; compared with the traditional polyimide film without adding modified silica aerogel, the performance change is small, the tensile strength is ≥300MPa, the elongation at break is ≥60%, the electrical strength is ≥300kV / mm, and the pinhole and bubble occurrence rate of the film is less than 0.1 / 1000m 2 .
[0021] Compared with the prior art, the present invention firstly modifies the silica aerogel with terminal hydroxyl polydimethylsiloxane, so that the terminal hydroxyl polydimethylsiloxane is combined with the active groups on the surface of the silica aerogel to reduce the -OH functional groups on the surface of the silica aerogel; then, small molecule diethoxydimethylsilane or dimethyldimethoxysilane is further used to chemically bond the silica aerogel whose surface is not completely modified by the terminal hydroxyl polydimethylsiloxane, so that the surface of the silica aerogel is mainly hydrophobic Si-CH3, and the S i-OH, Si-OC2H5 or Si-OCH3 functional groups of dimethylsiloxane; finally, the obtained modified silica aerogel is compounded with a polyimide film to improve the compatibility of the film surface with the epoxy resin in the epoxy adhesive sheet, so that the Si-OH of the terminal hydroxy dimethylsiloxane, the Si-OC2H5 or Si-OCH3 functional groups of dimethylsiloxane and the glass fiber are further combined; on the other hand, the modified silica aerogel has a large specific surface area, which can significantly increase the surface roughness of the film, further playing a role in enhancing the bonding force. Therefore, the polyimide film prepared by the method of the present invention has a satisfactory peel strength with the epoxy adhesive sheet. DETAILED DESCRIPTION
[0022] In order to better explain the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments, but the embodiments of the present invention are not limited thereto.
[0023] Example 1
[0024] 1) Preparation of modified silica aerogel
[0025] 1 kg of 20 nm silica aerogel was placed in 9 kg of anhydrous ethanol and ultrasonically dispersed for 1 h, then 100 g of hydroxy-terminated polydimethylsiloxane with a molecular weight of 10,000 was added, stirred evenly, ultrasonicated for 1 h, and then 10 g of diethoxydimethylsilane was added, stirred evenly, and ultrasonicated for 1 h to obtain a silica aerogel dispersion;
[0026] The container containing the silica aerogel dispersion is connected to an exhaust condensation and anhydrous ethanol recovery device, the dispersion in the container is stirred while being ultrasonically treated, and the anhydrous ethanol in the container is continuously volatilized, condensed and recovered until powder is precipitated, and the stirring is continued to disperse the powder under the condition of ultrasonic vibration until the powder is dry, thereby obtaining the modified silica aerogel;
[0027] 2) Preparation of polyamic acid solution
[0028] 1 kg of modified silica aerogel and 20 kg of N,N-dimethylacetamide were placed in a shearing machine at 1500 rpm for 1 hour, and then placed in an ultrasonic machine for 1 hour (40 Hz). The resulting liquid was poured into a reactor containing 400 kg of DMAc, and then 48 kg of ODA was added. After dissolving for 30 minutes, 50 kg of PMDA (added in 4 times) was slowly added to react. After stirring evenly, 2 kg of PMDA (added in 3 times) was slowly added, and the mixture was stirred for reaction for 2 hours to obtain a polyamic acid solution.
[0029] 3) Preparation of polyimide film with high peel strength
[0030] The obtained polyamic acid solution is defoamed, and then extruded onto a steel belt through an extrusion die and heated to obtain a self-supporting film. The obtained self-supporting film is longitudinally stretched at 120°C (stretching ratio is 5%) and then sent to an imidization furnace, transversely stretched for 2 minutes at a temperature of 120-250°C (stretching ratio is 10%), and then gradually heated at 450°C for imidization for 4 minutes, then slowly cooled to room temperature, and taken out of the imidization furnace to obtain a polyimide film, which is the polyimide film with high peel strength.
[0031] Example 2
[0032] Example 1 was repeated, except that in step 1), the amount of diethoxydimethylsilane used was 20 g.
[0033] Example 3
[0034] Example 1 was repeated, except that in step 1), the amount of diethoxydimethylsilane used was 1 g.
[0035] Example 4
[0036] Example 1 was repeated, except that in step 1), the molecular weight of the hydroxy-terminated polydimethylsiloxane was 50,000.
[0037] Example 5
[0038] Example 1 was repeated, except that in step 1), the molecular weight of the hydroxy-terminated polydimethylsiloxane was 500.
[0039] Example 6
[0040] Example 1 was repeated, except that in step 1), the amount of hydroxy-terminated polydimethylsiloxane added was 50 g.
[0041] Example 7
[0042] Example 1 was repeated, except that in step 1), the amount of hydroxy-terminated polydimethylsiloxane added was 200 g.
[0043] Example 8
[0044] Example 1 was repeated, except that in step 1), the amount of anhydrous ethanol added was 11.5 kg.
[0045] Example 9
[0046] Example 1 was repeated, except that in step 1), the amount of anhydrous ethanol added was 24 kg.
[0047] Example 10
[0048] Example 1 was repeated, except that in step 2), the amount of modified silica aerogel added was 500 g.
[0049] Embodiment 11
[0050] Example 1 was repeated, except that in step 2), the amount of modified silica aerogel added was 3 kg.
[0051] Example 12
[0052] Example 1 was repeated, except that the shear speed in step 2) was 1000 rpm, and the aromatic diamines were ODA and PDA, as follows:
[0053] 2) 1 kg of modified silica aerogel and 20 kg of N,N-dimethylacetamide were placed in a shearing machine at 1000 rpm for 1 hour, and then placed in an ultrasonic machine for 1 hour (40 Hz). The resulting liquid was poured into a reactor containing 400 kg of DMAc, and then 40 kg of ODA and 4.3 kg of PDA were added. After dissolving for 30 minutes, 50 kg of PMDA (added in 4 times) was slowly added to react. After stirring evenly, 2 kg of PMDA (added in 3 times) was slowly added, and the mixture was stirred for reaction for 2 hours to obtain a polyamic acid solution.
[0054] Example 13
[0055] Example 1 was repeated, except that the ultrasonic time during dispersion of the modified silica aerogel in step 2) was 2 h, and the aromatic dianhydride was PMDA and BPDA, as follows:
[0056] 2) 1 kg of modified silica aerogel and 20 kg of N,N-dimethylacetamide were placed in a shearing machine at 1000 rpm for 1 hour, and then placed in an ultrasonic machine for 2 hours (40 Hz). The resulting liquid was poured into a reactor containing 400 kg of DMAc, and then 48 kg of ODA was added. After dissolving for 30 minutes, 13.4 kg of BPDA was added, and then 40 kg of PMDA was slowly added (added in 3 times) to react. After stirring evenly, 2 kg of PMDA was slowly added (added in 2 times), and the reaction was stirred for 2 hours to obtain a polyamic acid solution.
[0057] Embodiment 14
[0058] Example 1 was repeated, except that the particle size of the silica aerogel was 1 μm.
[0059] Embodiment 15
[0060] Example 1 was repeated, except that the particle size of the silica aerogel was 200 nm.
[0061] Comparative Example 1
[0062] No modified silica aerogel is added when preparing the polyimide film. The details are as follows:
[0063] In a reactor filled with 400 kg of DMAc, 48 kg of ODA was added and dissolved for 30 minutes, and then 50 kg of PMDA (added in 4 times) was slowly added for reaction. After stirring evenly, the remaining 2 kg of PMDA was slowly added (added in 3 times), and the reaction was stirred for 2 hours to obtain a polyamic acid solution; the obtained polyamic acid solution was sent to a defoaming kettle for defoaming, and then extruded on a steel belt through an extrusion die and heated to obtain a self-supporting film. The obtained self-supporting film was imidized according to the same stretching and imidization process as in Example 1 to obtain a polyimide film.
[0064] Comparative Example 2
[0065] Comparative Example 1 was repeated, except that a 50% by mass KH550 anhydrous ethanol dilution was coated on the surface of the polyimide film prepared in Comparative Example 1.
[0066] Comparative Example 3
[0067] Comparative Example 1 was repeated, except that 10% by mass of KH550 anhydrous ethanol hydrolyzate was coated on the surface of the polyimide film prepared in Comparative Example 1, and distilled water and dilute hydrochloric acid were added to the hydrolyzate, the molar amount of distilled water was 2.5 times that of KH550, and the pH value of the hydrolyzate was 3-4.
[0068] Comparative Example 4
[0069] Comparative Example 1 was repeated, except that KH550 was added to the polyimide, as follows:
[0070] In a reactor filled with 400kg DMAc, 300g KH550 was added, and after stirring, 48kg ODA was added and dissolved for 30min, and then 50kg PMDA was slowly added (added in 4 times) for reaction. After stirring, the remaining 2kg PMDA was slowly added (added in 3 times), and the reaction was stirred for 2h to obtain a polyamic acid solution; the obtained polyamic acid solution was sent to a defoaming kettle for defoaming, and then extruded on a steel belt through an extrusion die and heated to obtain a self-supporting film. The obtained self-supporting film was imidized according to the same stretching and imidization process as in Example 1 to obtain a polyimide film.
[0071] Comparative Example 5
[0072] Steps 2) and 3) of Example 1 were repeated, except that the silica aerogel was not modified and “1 kg modified silica aerogel” was replaced with “1 kg 20 nm silica aerogel”.
[0073] Comparative Example 6
[0074] Example 1 was repeated, except that in step 1), diethoxydimethylsilane was not added, and only hydroxy-terminated polydimethylsiloxane was used to modify the silica aerogel.
[0075] Comparative Example 7
[0076] Example 1 was repeated, except that in step 1), the amount of diethoxydimethylsilane added was 0.9 g.
[0077] Comparative Example 8
[0078] Example 1 was repeated, except that in step 1), the amount of diethoxydimethylsilane added was 21 g.
[0079] Comparative Example 9
[0080] Example 1 was repeated, except that in step 1), no hydroxy-terminated polydimethylsiloxane was added, and only diethoxydimethylsilane was used to modify the silica aerogel.
[0081] Comparative Example 10
[0082] Example 1 was repeated, except that in step 1), the molecular weight of the hydroxy-terminated polydimethylsiloxane was 60,000 and the amount added was 200 g.
[0083] Comparative Example 11
[0084] Example 1 was repeated, except that in step 1), the amount of hydroxyl-terminated polydimethylsiloxane added was 40 g.
[0085] Comparative Example 12
[0086] Example 1 was repeated, except that in step 1), the amount of hydroxy-terminated polydimethylsiloxane added was 300 g.
[0087] Comparative Example 13
[0088] Example 1 was repeated, except that in step 2), the amount of anhydrous ethanol added was 5 kg.
[0089] Comparative Example 14
[0090] Example 1 was repeated, except that in step 2), the amount of modified silica aerogel added was 4 kg.
[0091] Comparative Example 15
[0092] Example 1 was repeated, except that in step 2), the amount of modified silica aerogel added was 0.5 kg.
[0093] Comparative Example 16
[0094] Example 1 was repeated, except that in step 1), the particle size of the silica aerogel was 2 μm.
[0095] Comparative Example 17
[0096] Example 1 was repeated, except that step 1) was omitted, and steps 2) and 3) were directly performed, and 1 kg of modified silica aerogel in step 2) was replaced with an equal amount of commercially available hydrophobic silica aerogel with a particle size of 20 nm produced by a certain manufacturer.
[0097] The main parameters in the above embodiments and comparative examples are summarized in the following Table 1.
[0098] Table 1:
[0099]
[0100]
[0101] The applicant tested the tensile strength, elongation at break and electrical strength of the polyimide films prepared in the above-mentioned embodiments and comparative examples, and stacked the obtained polyimide film with an epoxy adhesive sheet and a copper foil (the obtained polyimide film was placed between the epoxy adhesive sheet and the copper foil, and the side of the polyimide film in contact with the epoxy adhesive sheet was corona treated, while the side of the polyimide film in contact with the copper foil was not corona treated) and then pressed together to prepare a test sample to test the peel strength of the polyimide film obtained by the method of the present invention against the epoxy adhesive sheet and the copper foil. The results are shown in Table 2 below.
[0102] Table 2:
[0103]
[0104]
[0105] In the above Table 2, the tensile strength and elongation at break were tested using a universal tensile machine, and the electrical strength test was tested in accordance with the standard GB / T 13542.2-2009. The peel strength test was tested in accordance with IPC TM-650 5.5.3.4-1998. The test sample was prepared in the following manner: PET film (as a protective film), epoxy adhesive sheet, polyimide film (the side in contact with the epoxy adhesive sheet was corona treated), and copper foil were stacked in order from top to bottom to form a four-layer pre-pressed plate, and then pressed at a high temperature of 180°C for 30 minutes to obtain the test sample.
Claims
1. A method for preparing a polyimide film with high peel strength, comprising the following steps: 1) dispersing silica aerogel in anhydrous ethanol, modifying it with terminal hydroxyl polydimethylsiloxane and diethoxydimethylsilane in sequence, or modifying it with terminal hydroxyl polydimethylsiloxane and dimethyldimethoxysilane in sequence to obtain a dispersion, recovering the solvent from the dispersion to obtain a modified silica aerogel; wherein, The amount of anhydrous ethanol is such that the concentration of silica aerogel in the control system is less than or equal to 15wt%; The particle size of the silica aerogel is 10nm~1μm; The molecular weight of the terminal hydroxyl polydimethylsiloxane is 500-50000, and the amount of the terminal hydroxyl polydimethylsiloxane is 5-20wt% of the silica aerogel; The amount of diethoxydimethylsilane or dimethyldimethoxysilane is 0.1-2wt% of the silica aerogel; 2) dispersing the modified silica aerogel in a polar aprotic solvent, and then adding aromatic diamine and aromatic dianhydride to carry out polymerization reaction to obtain a polyamic acid solution; the amount of the modified silica aerogel is 0.5-3wt% of the total amount of the aromatic diamine and the aromatic dianhydride; 3) The obtained polyamic acid solution is prepared into a polyimide film, and the obtained film is subjected to or not subjected to corona treatment to obtain the polyimide film with high peel strength.
2. A polyimide film with high peel strength prepared by the method according to claim 1.
Citation Information
Patent Citations
Novel polyimide film with improved adhesiveness
CN101098909B
Polyimide film with high peel strength and preparation method thereof
CN106432723A
Super heat insulation coating containing polyimide aerogel microspheres and preparation method thereof
CN104629583A
Heat conduction polyimide film
CN107652432A